Identifying preface in the Qur’anic Surahs a new methodology of Qur’anic Interpretation” - Khan, Israr Ahmad (Centre of Qur'anic Research, UM, 2014)
It is a universally established fact that effective speech and writing comprise some basic and interconnected components such as preface, central theme, contextual flow, and conclusion. Absence of any of these elements may mar the beauty and effect of speech and writing. There is unanimity among Muslims, masses as well as scholars, over the Qur’an as the most effective speech revealed by Allah. The main reason for this quality of the Qur’an, as agreed by all Muslim scholars, is its inimitability (i‘jaz al-Qur’an). Yet, it is unbelievably surprising that most of the mufassirun (commentators of the Qur’an) right from the early periods of Islamic history until today ignored the task of identifying various components of Qur’anic Surahs and establishing link among them. Some commentators like Qazi Abd al-Jabbar, al-Haralliyy, al-Razi, al-Biqa’i, Syed Qutb, Syed Mawdudi, al-Farahi, and Islahi did attempt in their commentaries of the Qur’an to interpret the Surahs as thematically coherent by identifying link among various components of each and every single Surah. Some of them simply tried to show the link among all the verses of Qur’anic Surahs; and some others identified various themes in a Surah and suggested possible link among them. It appears that no commentator paid attention to identifying preface in Qur’anic Surahs, particularly large ones. It may not be imaginable that the Qur’anic Surahs do not have introductory part. The claim that preface does not exist in Qur’anic Surahs controverts the belief that the Qur’an is the most effective speech. This paper represents a humble attempt to research that each and every single surah, short or large, contains one or the other preface, at times, spreading over several verses in the beginning and, at times, covering only the first one or two verses. With the identification of preface in a Surah, the task of interpretation may become easier than ever before. This paper is divided into two main parts: (1) framework and role of preface in the interpretation of the Qur’an, and (2) identification of preface in some Surahs and its link to the rest of the verses in the particular Surah